Chilled Storage Studies of Depurated Cooked Clam Meat in two different Packaging Materials - Sreedevi, K. H.; James, J. P.; Bindu, J.; Sreejith, S.; Gopal, Nikita (Fishery Technology, 2018)
The biochemical and microbiological parameters ofdepurated cooked meat of black clam (Villoritacyprinoides) (Gray, 1825) was assessed for theextension of shelflife in iced condition in twodifferent packaging materials viz., Polyester polyethylenelaminate (PEST-PE) and low density polyethylene(LDPE). Aerobic plate count revealed that theshelflife of black clam was 22 days in PEST-PE and16 days in LDPE during which the count reached5.38 log cfug-1 and 4.9 log cfug-1, respectively. Theclam meat stored in LDPE had a TBA value of 1.36mg MDAkg-1 on 16th day and it was 1.23 mgMDAkg-1 for PEST-PE packed meat on the 22nd day.The values of TVB-N was 7.0 mg% and 7.4 mg%after 16 days and 22 days in the LDPE and PESTPE,respectively. Since the value of APC was 5.38 logcfug-1 on the 16th day for clam meat packed in LDPEit was not analysed further as the microbiologicalcount exceeded the limit of acceptability. From thisstudy it is inferred that the shelflife of clam meatmay be extended by proper icing after packaging insuitable packing material like PEST-PE.